High-accuracy height differences using a pressure sensor for ground control points measurement in underwater photogrammetry - F. Menna; E. Nocerino; A. Calantropio (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2024)
Three-dimensional reference points (RPs) are fundamental for datum definition and metric validation in many photogrammetric applications, often used as ground control points (GCPs) to constrain the bundle adjustment solution. Nevertheless, survey operations underwater present challenges due to the physical characteristics of the water itself and the technological limitations of available instruments. Traditional methods to collect RPs underwater rely on direct geodetic measurements like slope distances, height differences, and depths from a dive computer. These methods can be time-consuming and impractical to scale up to large areas, particularly in deeper waters. This paper reports on the use of a custom-developed low-cost pressure sensor to measure depths and height differences of underwater RPs with survey-grade accuracy. Laboratory and open water tests demonstrated the method's potential, achieving an RMSEZ of less than 1 mm over a 1.5 m height range in the laboratory in static water and a sub-centimetre RMSE of relative depth differences in shallow water tests carried out in two different locations at sea with maximum significant wave height of 9 cm. The sensor proved its effectiveness also for constraining a corridor-like underwater photogrammetric survey reducing the bending of the 3D model with respect to the free network solution (RMSEZ lowered from 10 cm to less than 1 cm). The preliminary tests with the presented approach proved several advantages against other consolidated methods, including cost reduction (compared to commercial survey instruments), rapidity, safety, and accuracy, especially at depths greater than 3–5 m where other approaches (e.g., GNSS or topographic measures) cannot be applied.